Effect of exogenous gonadotrophin and physical condition of goat on efficacy of superovulation and embryo transfer techniques / Md. Rokibur Rahman - Rahman, Md. Rokibur (2014)
Present research was carried out with the main objective to determine the effect of different sources and combinations of gonadotrophin for superovulation on ovarian responses and subsequent embryo transfer (ET) performance in goats. A total of 5 experiments had been designed. In Experiment 1, effect of supplementation of human chorionic gonadotrophin (hCG) or gonadotrophin releasing hormone (GnRH) on ovulation and subsequent embryo production of equine chorionic gonadotrophin (eCG) superovulated does were evaluated. In Experiment 2, effect of supplementation of hCG or GnRH on ovulation and subsequent embryo production of follicle stimulating hormone (pFSH) superovulated does were evaluated. The suitable gonadotrophin was selected from Experiments 1 and 2 for further research. In Experiment 3, effect of pFSH dosage based on body weight (BW) (3, 5 and 8 mg pFSH per kg BW) on superovulation performance was evaluated. In Experiment 4, effects of donor age (2-4 yr and >4 yr) and body weight (BW) (15-25 kg and >25 kg) on superovulation were evaluated. In Experiment 5, effect of recipient physical condition (surgery cycle) on pregnancy rate and subsequent kidding were evaluated. Oestrus was synchronised with a controlled intravaginal drug release device (CIDR) for 14 days and an i.m. injection of prostaglandin F2α (PGF2α) was carried out on Day 11. Subsequently superovulation was performed by using the exogenous gonadotrophin (eCG or pFSH) and initially administered on Day 12. eCG was administered with1500 IU in a single injection and pFSH was administered with 6 decreasing dosages (0800 to 0900 hr and 1900 to 2000 hr) for 3 consecutive days. After CIDR removal, oestrus was observed 3 times every day. Natural mating and artificial insemination (AI) were performed after showing the oestrus. Recipient does synchronisation for ET was carried out by inserting CIDR for 14 days and an i.m. injection of 300 IU eCG on Day 12. Embryo flushing from donor does were carried out during the laparotomy session on Day 7 after CIDR removal, and subsequently embryos were transferred to the recipient does. The findings of the present research were as follows: a) hCG supplementation was needed for eCG-superovulated donor does for better ovulation synchronisation and structures recovery; b) for pFSHsuperovulated donor does, no difference was observed among the treatment groups; c) pFSH dosage based on BW had a significant effect on embryo production performances and 5 mg pFSH per kg BW performed better for embryo production; d) the donor does of 2 to 4 years of age and more than 25 kg BW performed better on the ovulation and embryo production performances; e) intact recipient does produced significantly higher number of pregnancy after ET than the recipient does used for different surgeries earlier. In conclusion, it was suggested that the dosage based on per kg BW as well as age and BW of the donor does affected the performances in ovarian response and embryo production of superovulated donor does for ET programme.